Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan Dengan Corporate Social Responsibility dan Good Corporate Governance sebagai Variabel Pemoderasi (Studi Pada Perusahan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2010-2014) - Erdianty, Ratri Werdi; Bintoro, Imam (Universitas Muhammadiyah Yogyakarta, 2015)
This research aims to excamine the influence of financial performance on firm value with corporate social responsibility and good corporate responsibility as moderating variable. The object on his research is manufacturing companies was listed in Indonesian Stock Exchange in 2010-2014. This research used purposive sampling, and getting 21 companies with 130 observed data. The data analysis was conducted by using multiple regresion analysis.The results after analysis is financial performance (with ROA proxy) has not influence to firm value, financial performance with corporate social responsibility as moderating variable has positive influence to firm value. Meanwhile financial performance with good corporate responsibility (with management ownership proxy) as moderating variable has not influence to firm value.